2009
DOI: 10.1093/mutage/gep053
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of neutrophils and hypochlorous acid

Abstract: Chronic inflammation has been recognized as a contributing factor in the pathogenesis of lung cancer. In this process, reactive oxygen species released by neutrophils may play an important role. The aim of the present study was to investigate the capacity of the major neutrophilic oxidant hypochlorous acid (HOCl), which is formed by myeloperoxidase (MPO), to induce DNA damage and mutagenicity in lung cells. HOCl was mutagenic in lung epithelial A549 cells in vitro, showing at physiological concentrations a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(125 citation statements)
references
References 39 publications
4
120
0
1
Order By: Relevance
“…53,55 FA exposure also leads to inflammation and to a consequent excess of ROS. 31,56 ROS, as hydrogen peroxide and hypochlorite acid, are indeed generated from the oxidative burst of activated alveolar macrophages and neutrophils. 31 The genomic mechanisms of instability and the cellular tolerance pathways associated with FA exposure seem to be a key point in the mutation arising, even if it is not fully characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,55 FA exposure also leads to inflammation and to a consequent excess of ROS. 31,56 ROS, as hydrogen peroxide and hypochlorite acid, are indeed generated from the oxidative burst of activated alveolar macrophages and neutrophils. 31 The genomic mechanisms of instability and the cellular tolerance pathways associated with FA exposure seem to be a key point in the mutation arising, even if it is not fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…31,56 ROS, as hydrogen peroxide and hypochlorite acid, are indeed generated from the oxidative burst of activated alveolar macrophages and neutrophils. 31 The genomic mechanisms of instability and the cellular tolerance pathways associated with FA exposure seem to be a key point in the mutation arising, even if it is not fully characterized. 57 Many studies have shown that FA is genotoxic and mutagenic in vitro in various kinds of mammalian cells including cultured human blood and human nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, neutrophils were shown to directly promote tumorigenesis by causing genomic instability [257]. Neutrophil-induced genotoxicity has been related to induction of oxidative DNA damage through release of ROS and myeloperoxidase-related metabolites [258][259][260]. In addition, neutrophils were shown to promote experimental chronic colitis-associated carcinogenesis in mice [261].…”
Section: Neutrophils In Tumor Initiation -Inflammation-associated Tummentioning
confidence: 99%
“…Neutrophils have been reported to increase cancer genetic instability by their production of nitric oxide derivatives and reactive oxygen species (5), to promote angiogenesis by their secretion of pro-angiogenic factors (6,7), and also to produce immunosuppressive factors, such as IL-10 (8). For all these reasons, neutrophil infiltration of several solid tumors has been associated with a poorer outcome for patients (9).…”
Section: Introductionmentioning
confidence: 99%